UTILIZING READALOUD ACTIVITIES TO DRIVE ADOLESCENT STRUGGLING READERS’ ENTHUSIASM TO READING - Zuno, Zuninho Adha; Mulyani, Martina (English Education Department of STKIP Pasundan, 2026)
The HIMABI (English Student Association) Mengajar program is aimed at addressing literacy issues in Cimahi and West Bandung Regency. This study, framed within the context of the program, attempted to investigate students' enthusiasm for reading through read-aloud activities. Adopted a case study approach and utilized observation and interviews for data collection. The study selected four adolescents from an elementary school in Padalarang, West Bandung, as participants. The concept of enthusiasm was pivotal in understanding students' engagement with reading. Indicators such as gestures, vocal delivery, facial expressions, eye contact, and overall energy were analyzed to assess their enthusiasm. Findings revealed that read-aloud activities allowed instructors to demonstrate proper reading intonation and expression, providing students with a model to emulate. This not only fostered listening skills but also built students' confidence in their reading abilities. Students displayed clear attentiveness, characterized by enthusiastic expressions and occasional nods while rereading passages. These positive indicators suggest that engaging in read-aloud sessions significantly enhances students' enthusiasm for reading. The study concludes that read-aloud activities can be an effective strategy for cultivating a love for reading among students, encouraging them to become more invested in their literacy development. Overall, the research supports the idea that structured reading activities can effectively raise students' interest and engagement.